Peptide Signaling during Plant Reproduction. (August 2021) - Kim, Min-Jung; Jeon, Byeong Wook; Oh, Eunkyoo; Seo, Pil Joon; Kim, Jungmook
Abstract : Plant signaling peptides are involved in cell–cell communication networks and coordinate a wide range of plant growth and developmental processes. Signaling peptides generally bind to receptor-like kinases, inducing their dimerization with co-receptors for signaling activation to trigger cellular signaling and biological responses. Fertilization is an important life event in flowering plants, involving precise control of cell–cell communications between male and female tissues. Peptide-receptor-like kinase-mediated signaling plays an important role in male–female interactions for successful fertilization in flowering plants. Here, we describe the recent findings on the functions and signaling pathways of peptides and receptors involved in plant reproduction processes including pollen germination, pollen tube growth, pollen tube guidance to the embryo sac, and sperm cell reception in female tissues. Highlights: Accumulating evidence suggests that peptide hormones play critical roles in coordinating male–female gametophyte interactions for successful plant reproduction processes through receptor-like kinase-mediated signaling in flowering plants. During the self-incompatibility response in Brassica napus, the interaction of S-LOCUS RECEPTOR KINASE (SRK) receptor with its ligand S-LOCUS CYSTEINE RICH PROTEIN/S-LOCUS PROTEIN11 (SCR/SP11) causes ARMADILLO-REPEAT-CONTAINING1 (ARC1) to mediate proteosomal degradation of compatibility factors, leading to pollen rejection. LURE peptide-mediated signaling is critical for pollen tube guidance and reproductive isolation in arabidopsis ( Arabidopsis thaliana ). A male and female-derived peptide ligand switching mechanism allows pollen tube maintenance and pollen tube rupture for sperm release to be spatiotemporally regulated. Two FERONIA (FER) receptor-dependent processes, deposition of de-esterified pectin, and an increase in nitric oxide levels, enable the prevention of polyspermy to ensure reproductive success.